Big Data-Driven Information Security Behavioural Profiling For Organisational Resilience - Najwa Hayaati Mohd Alwi; Hanifah Abdul Hamid; Azni Haslizan Ab Halim; Farida Hazwani Mohd Ridzuan; Odai Enaizan (Karya Ilham Publishing, 2026)
Indexed by MyCite